THE RULE OF DECENTRALIZATION EQUALS TO LOCAL SELF-GOVERNMENT? GENERAL REMARKS ON LOCAL DEMOCRACY IN THE U.S. AN INTRODUCTION TO NEW EXPLORATIONS - Maćkowska, Katarzyna (Review of European and Comparative Law, 2018)
This article refers to a problem of democracy at local levels in the United States. Decentralization of public administration in a federal state raises many questions about local-self government and local democracy. Therefore, a brief introduction is hereby presented, including the following aspects: status of local units, home rule charters, and the managerial system at a local level. When necessary, short references to continental solutions are made in order to explain specific American local structures. Historical determinants are also mentioned in order to illustrate that the U.S. system does not pose an ideal and universal democracy, but there are many provisions that should be considered as a pattern. It is especially significant in the aspect of civil society and its role in contemporary democracy.